Factors associated with under-five mortality in Bhutan: an analysis of the Bhutan National Health Survey 2012 - Tashi Dendup; Yun Zhao; Deki Dema (BMC, 2018)
Abstract Background As an important marker for health equity and access, under-five mortality (UFM) is a primary measure for socioeconomic development. The importance of reducing UFM has been further emphasized in an ambitious target under Sustainable Development Goals. The factors influencing UFM are not adequately understood in Bhutan. Methods The most recent dataset of the Bhutan National Health Survey (BNHS) 2012 was used in this study. Multiple logistic regression analysis using a backwards elimination approach was performed to identify significant factors influencing UFM. All statistical analyses were adjusted for the complex study design due to the multistage stratified cluster sampling used in BNHS. Results Bhutan's UFM rate was 37 per 1000 live births. The weighted mean age of the children was 7.3 years (SD: 1.53; range: 3-12). Mother's age, household size, access to electricity and sanitation, residential region, and parity were the key factors associated with UFM. The UFM risk was significantly lower in children born to mothers aged 36-40 years, 41-45 years, and > 45 years when compared to that in children born to mothers aged < 26 years. The likelihood of mortality was 66% lower (95% CI: 0.21-0.55) among children born in households with > 5 members. Children born in households without electricity and safe sanitation had a significantly higher risk of death, by 81 and 49% respectively. Relative to those born in the west, children born in the central and eastern regions were 1.72 (95% CI: 1.07-2.77) and 2.09 (95% CI: 1.46-2.99) times more likely to die, respectively. Children born to mothers who gave birth to > 2 children were significantly more likely to die than their counterparts. Conclusion These findings suggest that younger mother's age, the higher number of births and being born in the central and eastern regions are associated with a higher UFM risk, whereas a larger household size and access to electricity and safe sanitation are key factors associated with lower UFM risk in Bhutan. Women empowerment, health education and strategies promoting maternal and child health in rural areas need to be scaled-up. Additionally, socioeconomic development programs should seek to reduce regional disparities.